Comparison of different types of cardiac amyloidosis by cardiac magnetic resonance imaging. (June 2015) - Kristen, Arnt V.; aus dem Siepen, Fabian; Scherer, Katrin; Kammerer, Rebekka; Andre, Florian; Buss, Sebastian J.; Bauer, Ralf; Lehrke, Stephanie; Voss, Andreas; Giannitsis, Evangelos; Katus, Hugo A.; Steen, Henning
Abstract Objectives: We sought to determine cardiac morphological and functional differences between light-chain (AL), mutant-type transthyretin (ATTRmt) and wild-type TTR (ATTRwt) amyloidosis using contrast-enhancement cardiac magnetic resonance imaging (CE-CMR). Finally, we attempted to establish the diagnostic and prognostic impact of these findings. Introduction: The most common forms of cardiac amyloid are AL and ATTR amyloidosis, but the clinical courses of these variants are quite heterogeneous. While CE-CMR is used to evaluate patients with cardiac amyloidosis, its ability to predict prognosis in these patients is debatable. Methods: About 130 patients with cardiac amyloidosis (AL, n = 62; ATTRmt, n = 30, ATTRwt, n = 33) were assessed by CE-CMR (cardiac morphology, cardiac function, late gadolinium enhancement). Results: Left ventricular (LV) mass, basal and mid-ventricular maximal wall thickness, and thickness of the inter-atrial septum were higher in ATTRwt when compared to AL and ATTRmt amyloidosis. Tricuspid annular excursion was lower in ATTRwt amyloidosis than in AL amyloidosis. CE was observed in 94.6% of the patients (AL 80.6%; ATTRmt 90%; ATTRwt 87.9%) with significant differences in quality and intensity between the groups. Differentiation of amyloid types was achieved by combination of age, number of organs, the presence of inferolateral CE-CMR, thickness of inter-atrial septum and troponin T. Overall 1-year-survival rates were 93.3, 93.9 and 70.5% in ATTRwt, ATTRmt and AL amyloidosis, respectively. LV mass, mitral annular excursion and NT-proBNP in AL amyloidosis, LV mass maximal apical wall thickness and troponin T in ATTRwt amyloidosis, and finally NT-proBNP and renal function in ATTRmt amyloidosis were independent predictors of outcome. Conclusions: This study demonstrates that CE-CMR can highlight morphological and functional differences between different types of cardiac amyloidosis. In addition, CE-CMR and cardiac biomarkers provide useful prognostic information in patients with cardiac amyloidosis.